UJI EFEK EKSTRAK ETANOL 70% DAUN KUMIS KUCING (Orthosiphon stamineus) TERHADAP KADAR GLUKOSA DARAH TIKUS PUTIH JANTAN GALUR WISTAR YANG DIINDUKSI ALOKSAN - Fauzan, Iqbal Hilmi, Dr. dr. EM. Sutrisna, M.Kes (2017)
Abstract Orthosiphon stamineus is a traditional plant that has antidiabetic effect. Chemical substance in Orthosiphon stamineus leaf which can reduce blood glucose level is flavonoid. The mechanism of the compound is to inhibit glucose absorption in intestinal and regenerate β cell of pancreas so that can reduce blood glucose level. This study was experimental laboratory using pre and post test with controlled group design method. The animals that were used 25 male white rats wistar strain and were divided into 5 treatment groups : sterile distilled water (negative control), glibenclamide (positive control), 70% extract of Orthosiphon stamineus leaf with the dose of 0.25, 0.75 and 1.25 g/kg of bodyweight. Based on Kruskal-Wallis test was obtained a significant probability value p = 0.000 means there was differences on blood glucose level reduction is significant. The dose of 0.25, 0.75 and 1.25 g/kg of bodyweight show better reduction compared to using sterile distilled water, but only the dose of 1.25 g/kg bodyweight is as effective as glibenclamide if administered for 14 day. Keyword: The 70% Ethanolic extract of Orthosiphon stamineus leaf, blood glucose level